Pengaruh Pembiayaan Mudharabah dan Musyarakah Terhadap Profitabilitas Pada Bank Umum Syariah Di Indonesia - Wida Ayu Ningsih; Wirman Wirman (Peneliti.net, 2023)
This study aims to determine how much influence mudharabah and musyarakah financing have on profitability by using the Return On Assets (ROA) ratio. The objects in this study were the financial reports of Islamic Commercial Banks for the quarterly period 2017-2020 of 3 Islamic Commercial Banks and 48 financial statements were taken as a sample. In this study, the samples were taken using a purposive sampling technique. The method used for data collection uses secondary data. The analysis used uses multiple linear regression. The results showed that mudharabah and musyarakah financing simultaneously had a significant effect on profitability. The partial test results show that mudharabah financing has a significant positive effect on profitability while musyarakah financing also has no positive effect on profitability.